A systematic review of clinicians' views and experiences of direct‐acting oral anticoagulants in the management of nonvalvular atrial fibrillation. (22nd September 2018) - Generalova, Daria; Cunningham, Scott; Leslie, Stephen J.; Rushworth, Gordon F.; McIver, Laura; Stewart, Derek
Abstract : Aims: While a plethora of systematic reviews have provided evidence of efficacy, effectiveness and safety of direct‐acting oral anticoagulants (DOACs) in the management of nonvalvular atrial fibrillation, there has been little emphasis on clinicians' perspectives. This systematic review aimed to critically appraise, synthesize and present the available evidence of clinicians' views and experiences. Methods: Studies published in English from January 2006 to July 2017 reporting the views and/or experiences of doctors, nurses or pharmacists on any individual DOAC or as a pharmacological group were included. Studies were assessed for quality by two researchers, data extracted and findings synthesized using a narrative approach. Results: Following exclusion of duplicates, 777 titles, 394 abstracts and 196 studies were screened. Ten studies were included in the review, nine of which were quantitative (cross‐sectional surveys) and one qualitative (semistructured interviews), with marked heterogeneity in outcomes reported. Studies were conducted exclusively in Europe and the USA. In those studies reporting clinician preference, DOACs were first choice over warfarin in naïve patients, based on perceptions of evidence of effectiveness equivalent or superior to warfarin and superior safety. Other advantageous factors were in those with an unstable International Normalized Ratio and likely to miss appointments. There were, however, concerns relating to management of over‐anticoagulation and experiences of observed bleeding rates. Conclusion: There is a limited evidence base of clinicians' perspectives of DOACs, necessitating further research, particularly given the trajectory of increased use worldwide.